A Comparative Study of Stress among Undergraduate Medical and Non-Medical Students - Laibah Safdar, Ayesha Shahbaz, Saima Chaudry, Laibah Safdar, Ayesha Shahbaz, Saima Chaudry (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: To compare the levels of stress among undergraduate medical and non-medical students studying in different educational institutions of Rawalpindi and Islamabad, and assess the difference in these stress levels between the two groups. Methods: In this cross-sectional comparative study, a total of 120 students (including both male and female) in each of the two groups were taken by convenience sampling for questionnaire filling. Non-medical students belonged to disciplines of engineering, management science, computer science and social sciences. Medical students were taken from both government (Rawalpindi Medical College) and private (Shifa College of Medicine, Islamabad) medical colleges. The scale employed for data collection was General Health Questionnaire (GHQ) which has a score range from 0 to 28, with a cut off value of 4. Results: Among the 120 students taken in each group, 89 medical students and 107 non-medical students were found to be stressed. Also, the mean scores on GHQ for medical students came out to be 8.58 and for the non-medical students 10.23. Conclusion: The stress levels of undergraduate non-medical students are higher than those of undergraduate medical students in colleges and universities of Rawalpindi and Islamabad. There is a need for appropriate measures to be taken by the undergraduate non-medical students and the institutions where they study, to ensure a decline in the stress levels of these students, which is necessary for their better functioning. Key Words: Stress, Medical students, Non-medical students.